An Aldehyde Responsive, Cleavable Linker for Glucose Responsive Insulins. Issue 9 (15th January 2021) - Mannerstedt, Karin; Mishra, Narendra Kumar; Engholm, Ebbe; Lundh, Morten; Madsen, Charlotte S.; Pedersen, Philip J.; Le‐Huu, Priska; Pedersen, Søren L.; Buch‐Månson, Nina; Borgström, Björn; Brimert, Thomas; Fink, Lisbeth N.; et al.
Abstract: A glucose responsive insulin (GRI) that responds to changes in blood glucose concentrations has remained an elusive goal. Here we describe the development of glucose cleavable linkers based on hydrazone and thiazolidine structures. We developed linkers with low levels of spontaneous hydrolysis but increased level of hydrolysis with rising concentrations of glucose, which demonstrated their glucose responsiveness in vitro. Lipidated hydrazones and thiazolidines were conjugated to the LysB29 side‐chain of HI by pH‐controlled acylations providing GRIs with glucose responsiveness confirmed in vitro for thiazolidines. Clamp studies showed increased glucose infusion at hyperglycemic conditions for one GRI indicative of a true glucose response. The glucose responsive cleavable linker in these GRIs allow changes in glucose levels to drive the release of active insulin from a circulating depot. We have demonstrated an unprecedented, chemically responsive linker concept for biopharmaceuticals. Abstract : 463 Million people live with diabetes of which approximately 10 % have type 1 diabetes. A glucose responsive insulin that responds to fluctuations in blood glucose concentrations has remained an elusive goal for decades. Here we describe the chemical development of hydrazones and thiazolidines that are cleavable in glucose concentration dependent manner. These were used to construct unprecedented glucose responsive insulins.